Cymatosirella Dąbek, Witkowski & Sabbe gen. nov., a new marine benthic diatom genus (Bacillariophyta) belonging to the family Cymatosiraceae - Dąbek, Przemysław; Sabbe, Koen; Witkowski, Andrzej; Archibald, Colin; Kurzydłowski, Krzyszof J.; Zgłobicka, Izabela (Phytotaxa, 2014)
We present a new marine benthic diatom genus Cymatosirella gen. nov. The genus belongs to the family Cymatosiraceae and has been assigned to the subfamily Extubocelluloideae on the basis of ultrastructural cell wall features. It has isovalvate cells with undulate valves and is characterized by the absence of tubular processes and the occurrence of hollow spines which are observed for the first time in the Cymatosiraceae. The new genus contains four species, two of which are transferred from the genus Cymatosira, viz. Cymatosirella capensis comb. nov. and Cymatosirella minutissima comb. nov., and two which are new to science, viz. Cymatosirella benguelensis sp. nov. and Cymatosirella taylorii sp. nov. Cymatosirella capensis is chosen as the generitype. The new genus includes a group of very small taxa inhabiting the intertidal zone of the Atlantic Ocean with three species in South Africa and one in Europe. C. capensis was originally described by Giffen from Langebaan Lagoon (a shallow marine inlet in the southern part of Saldanha Bay, Western Cape Province), on the basis of light microscopy only, and has to date only been illustrated by line drawings. C. minutissima, so far only known from the Westerschelde estuary (The Netherlands), has previously been documented in more detail using both light and electron microscopy. Here, we present the results of detailed light and electron microscopical investigations of C. capensis, both from its original type material and from recently collected samples from the type locality and neighboring littoral areas in the Western Cape Province, and of the new species C. benguelensis and C. taylorii, also from Western Cape localities. All species are compared with similar small taxa belonging to the Cymatosiraceae, subfamily Extubocelluloideae.